2011
DOI: 10.4104/pcrj.2011.00012
|View full text |Cite
|
Sign up to set email alerts
|

Understanding what asthma plans mean: a linguistic analysis of terminology used in published texts

Abstract: Results: A wide range of asthma plan terminology was evident, with terms such as 'action plans', 'self-management plans' and 'treatment plans' being applied inconsistently and synonymously. For individual patients the term 'asthma plan' can describe a clinically-determined list of prescribed medication, an agreed plan to guide self-management of changing symptoms, or a more holistic 'living with asthma' plan. In some contexts the term 'asthma plan' was also used to describe an organisational system of care, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The terminology related to asthma programmes, plans, guidelines and strategies is confusing [50]. In this review, we define an asthma programme as an activity with: defined time frames; identified management and treatment problems; clear goals for planned activities; definition and implementation of strategies to achieve the goals; and results of the interventions.…”
Section: Methodsmentioning
confidence: 99%
“…The terminology related to asthma programmes, plans, guidelines and strategies is confusing [50]. In this review, we define an asthma programme as an activity with: defined time frames; identified management and treatment problems; clear goals for planned activities; definition and implementation of strategies to achieve the goals; and results of the interventions.…”
Section: Methodsmentioning
confidence: 99%
“…This comparison process allowed for recognition of their experiential asthma knowledge [7] with participants able to reflect upon the ways in which they had experienced and handled certain situations in regards to their asthma. Despite many participants reporting a high level of asthma knowledge prior to the study, many were still able to acquire hints and tips regarding the management of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of reasons for this, including forgetfulness [5], failure to accept being an asthma sufferer [6], and an over reliance on medical self management plans that fail to take account of the patients' experiential knowledge and the context of their daily lives [7]. There is little agreement, even between clinicians, about what good asthma control entails [8]; however knowledge appears to be important [9].…”
Section: Introductionmentioning
confidence: 99%
“…A rapid synthesis of the evidence on interventions supporting self-management for people with long-term conditions: PRISMS -Practical systematic RevIew of Self-Management Support for long-term conditions 21 Search Hypertension: summary of the included reviews' aims and key findings, as outlined in the study abstracts (copied directly from reviews' summaries) 222 …”
mentioning
confidence: 99%